2019
DOI: 10.1080/10871209.2019.1616238
|View full text |Cite
|
Sign up to set email alerts
|

Controlled exposure reduces fear of brown bears

Abstract: Fear of large carnivores such as brown bears may restrict people's outdoor activities regardless of experts' estimated risk of attack. This research study empirically examined three exposure interventions in the form of guided walks intended to give people living in brown bear areas tools for coping with their fear. All interventions significantly reduced fear, decreased people's perceived vulnerability, and increased their social trust in wildlife management authorities. The walk including an encounter with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 49 publications
(62 reference statements)
1
26
0
Order By: Relevance
“…Therefore, guided walks in brown bear areas may be a more efficient approach than information meetings indoors. Similar experiences could be promoted in wildlife parks and zoos (Johansson et al 2019).…”
Section: Addressing People's Fear In Large Carnivore Conservation: a mentioning
confidence: 86%
“…Therefore, guided walks in brown bear areas may be a more efficient approach than information meetings indoors. Similar experiences could be promoted in wildlife parks and zoos (Johansson et al 2019).…”
Section: Addressing People's Fear In Large Carnivore Conservation: a mentioning
confidence: 86%
“…Moreover, the affective experiences associated with a potential brown bear encounter comprising valence varying along unpleasantness-pleasantness and arousal varying along deactivation-activation can be altered, in particular by increasing a positive valence. Also, self-reported fear of an encounter has been shown to decrease (Johansson et al, 2016c(Johansson et al, , 2017(Johansson et al, , 2019. An effect on self-reported avoidance behavior has been identified for the guided walks.…”
Section: Previous Researchmentioning
confidence: 96%
“…The role of factual knowledge of the feared species in reducing fear is according to Field et al (2001) debatable, but practical knowledge of how to behave has been demonstrated to reduce fear and improve coping in encounters with the feared animal, at least among people with dog phobia (Hoffman and Odendaal, 2001;Hoffman and Human, 2003). Johansson et al (2016cJohansson et al ( , 2017Johansson et al ( , 2019 based on theory of human-environment interaction (Küller, 1991) and appraisal theory of emotion (Scherer, 2001), proposed that informational interventions aimed to reduce fear of brown bears must alter the individual's appraisal of a potential encounter with these animals. Arguing that the information content should relate to the aspect of coping potential of the appraisal of a potential encounter with the feared animal.…”
Section: Previous Researchmentioning
confidence: 99%
See 2 more Smart Citations